DO OLHAR MELANCÓLICO À POSSIBILIDADE ALEGÓRICA: UMA LEITURA DA POESIA DE MÁRIO DE ANDRADE SEGUNDO WALTER BENJAMIN - Bertussi, Lisana (Organon, 2004)
A study of Mário de Andrade’s poetry by means of the theoritical instruments offered by WalterBenjamin to read modernity. The “melancolic eye” as constructing the possible perspective of the sense beforefragments of the world.